Precision Forestry: Using Machine Learning and LiDAR to Inform Thinning in Pinus taeda Plantations – A Case Study - Erik Platt; David R. Carter; Amith Reddy; Timothy J. Albaugh; Rachel L. Cook; Otávio Campoe; Rafael Rubilar; Gunjan Barua; Matthew J. Sumnall (Journal of Forestry, 2026)
We demonstrate that the inputs and conceptual foundation needed for individual-tree-level precision thinning optimization algorithms are already available. As more resource managers adopt LiDAR-based inventories, precision thinning can become a value-added outcome of collecting these data. We use LiDAR to assess individual-tree stem volumes in Pinus taeda L. plantations in the southeast US. Rather than arbitrarily selecting starting rows in row thinning operations, we use field- and LiDAR-derived stem volume data to inform row selection. Among all three study sites, row-to-row tree volume variability was present, indicating that selecting rows to be removed deliberately could improve thinning outcomes. A machine learning model based on LiDAR-derived metrics was also accurate in estimating individual stem volume in the primary study site and LiDAR was accurate in measuring pre- and post-thinning stem counts, the data that would be needed to audit thins.

Carbon fluxes and partitioning in Eucalyptus and Pinus plantations across a climatic gradient in Brazil - Fernanda Leite Cunha; Otávio Camargo Campoe; Cléber Rodrigo de Souza; Isaira Leite & Lopes; Yann Nouvellon; Timothy Albaugh; David R. Carter; Rafael Rubilar; Isabel Deliberari; Rachel Cook; Joannès Guillemot; Guerric Le Maire; et al. (Agricultural and Forest Meteorology, 2026)

APAR is a better predictor than LUE of the stem growth differences found between Loblolly pine grown in the United State and Brazil - Lorena Oliveira Barbosa; Otávio Camargo Campoe; José Roberto Soares Scolforo; Henrique Ferraço Scolforo; Timothy J. Albaugh; Rachel Cook; Rafael Rubilar; Juscelina Arcanjo Santos (Agricultural and Forest Meteorology, 2026)

Precision forestry in actively managed loblolly pine plantations: Leaf area index response one growing season following a variable-rate fertilization - Chris W. Cohrs; Al Lyons; Timothy J. Albaugh; David R. Carter; Otávio C. Campoe; Rafael A. Rubilar; Matthew Sumnall; Andrew Trlica; Mark V. Corrao; Simerjeet Virk; Rex Lester; Rachel L. Cook (Forest Ecology and Management, 2025)

Predicting the yield of Pinus taeda (L.) using UAV LiDAR data in random forest and support vector machine models - Gunjan Barua; David R. Carter; Valerie A. Thomas; P. Corey Green; Phil Radtke; Thomas J. Pingel; Rachel L. Cook; Timothy J. Albaugh; Rafael Rubilar; Otavio Campoe; Matthew Sumnall (Forest Ecology and Management, 2025)

Quantifying above- and belowground biomass improved our understanding of site differences and demonstrated the importance of management decisions in sequestering carbon in Pinus taeda - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marshall A. Laviner; Timothy J. Shively; Vitor Aguiar; Kyle R. Peer; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Forest Ecology and Management, 2025)

Improved Estimates of Biomass Expansion Factors and Root‐To‐Shoot Ratios: An Approach for Different Forest Types Across a Climatic Gradient in Brazil - Isáira Leite e Lopes; Otávio Camargo Campoe; Geovanni Malatesta Barros; Anny Francielly Ataide Gonçalves; Gabriela Gonçalves Moreira Matzner; Marco Aurelio Figura; Clayton Alcarde Alvares; Fernanda Leite Cunha; Verônica Boarini Sampaio de Rezende; James Stahl; Josiana Jussara Nazaré Basílio; Hyngrid Jaiely Araújo Félix; et al. (Global Change Biology, 2025)
Advancements in the current state of the art of the key drivers of biomass expansion factor (BEF) and the root‐to‐shoot ratio ( R ) are crucial for producing accurate information on forest biomass and carbon stocks. Hence, we compiled a nationally representative dataset encompassing diverse tree growth stages and climatic gradients. In this study, we propose models to improve BEF and R estimates at the tree level for Eucalyptus and Pinus plantations in Brazil. In general, the BEF values were more representative (91.7%) in the database than the R values (8.3%) due to the high cost of collecting coarse roots. Regarding genera, Eucalyptus was more extensively sampled (89.9%) than Pinus (10.1%), reflecting the predominance of Eucalyptus as the most widely planted genus in Brazil. The average BEF and R values calculated in this study were 1.16 and 0.22, respectively, for Eucalyptus spp. and 1.22 and 0.31, respectively, for Pinus spp. In predicting the BEFs, the random effects in the linear mixed model that significantly captured the variations in Eucalyptus and Pinus spp. were temperature and age class, respectively. The fixed effects for Eucalyptus spp. included diameter, height, and age, while for Pinus spp., they were the Köppen climate classification, species, slenderness degree, and age. R estimates were mainly influenced by precipitation and age for both genera, with slenderness and diameter specifically affecting Eucalyptus spp., and height being a driving factor for Pinus spp. Our findings discourage the use of fixed or default values for BEF and R across locations with different climates and growing conditions to reduce uncertainties in carbon accounting and greenhouse gas inventories.

Evaluating individual tree metrics calculated from unmanned aerial vehicle laser scanning as input to a conventional growth and yield model - Matthew J. Sumnall; David R. Carter; Timothy J. Albaugh; Rachel L. Cook; Otávio C. Campoe; Rafael A. Rubilar (International Journal of Remote Sensing, 2025)

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Growth trends of loblolly pine age five or less in relation to soil type and management intensity - Christen Beasley; David R. Carter; Timothy J. Albaugh; David Enemo; Daniel S. Hong; Rachel Cook; Otávio Campoe; Rafael Rubilar (Forest Ecology and Management, 2024)

Nature vs. nurture: Drivers of site productivity in loblolly pine (Pinus taeda L.) forests in the southeastern US - Vicent A. Ribas-Costa; Aitor Gastón; Sean A. Bloszies; Jesse D. Henderson; Andrew Trlica; David R. Carter; Rafael Rubilar; Timothy J. Albaugh; Rachel L. Cook (Forest Ecology and Management, 2024)

Evaluating the transferability of airborne laser scanning derived stem size prediction models for Pinus taeda L. stem size estimation to two different locations and acquisition specifications - Matthew J. Sumnall; David R. Carter; Timothy J. Albaugh; Erik Platt; Trevor Host; Rachel L. Cook; Otávio C. Campoe; Rafael A. Rubilar (International Journal of Remote Sensing, 2024)

Forest soil classification for intensive pine plantation management: “Site Productivity Optimization for Trees” system - Rachel Cook; Thomas R. Fox; Howard Lee Allen; Chris W. Cohrs; Vicent Ribas-Costa; Andrew Trlica; Matthew Ricker; David R. Carter; Rafael Rubilar; Otávio Campoe; Timothy J. Albaugh; Pete Kleto; et al. (Forest Ecology and Management, 2024)

Pinus taeda carryover phosphorus availability on the lower Atlantic Coastal Plain - Jacob Hackman; Rachel Cook; Brian Strahm; David Carter; Alex Woodley; Kevin Garcia; Timothy Albaugh; Rafael Rubilar; Otavio Campoe (Forest Ecology and Management, 2024)

Rotation-age effects of subsoiling, fertilization, and weed control on radiata pine growth at sites with contrasting soil physical, nutrient, and water limitations - Rafael Rubilar; Daniel Bozo; Timothy Albaugh; Rachel Cook; Otávio Campoe; David Carter; H. Lee Allen; José Álvarez; Matías Pincheira; Álvaro Zapata (Forest Ecology and Management, 2023)

Estimation of individual stem volume and diameter from segmented UAV laser scanning datasets in Pinus taeda L. plantations - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2023)

Effect of varied unmanned aerial vehicle laser scanning pulse density on accurately quantifying forest structure - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2022)

Eucalyptus grandis Response to Calcium Fertilization in Colombia - Zach S Grover; Rachel L Cook; Marcela Zapata; J Byron Urrego; Timothy J Albaugh; Ariel Zelaya; Tomasz Ozyhar; Rafael Rubilar; David R Carter; Otávio C Campoe (Forest Science, 2021)
Calcium (Ca) is a critical plant nutrient typically applied at the time of planting in intensive Eucalyptus plantations in South America. At two sites in Colombia, we examined (1) calcium source by comparing growth after application of 100 kg ha−1 elemental Ca as lime or as pelletized highly reactive calcium fertilizer (HRCF) compared to a no application control, and (2) Ca rate by applying 0, 100, 200, and 400 kg ha−1 elemental Ca as HRCF with the addition of nitrogen, phosphorus, potassium, sulfur, and boron (NPKSB). We assessed height, diameter, and volume after 12 and 24 months. There were no growth differences from Ca source at the 100 kg ha−1 rate. We found increased volume after 24 months at the “Popayan” site with 200 and 400 kg ha−1 Ca HRCF+NPKSB treatments (112 and 113 m3 ha−1, respectively) compared to control (92 m3 ha−1), a 22% increase. In contrast, volume did not differ after 24 months at the “Darien” site, ranging from 114 m3 ha−1 in the 0 kg ha−1 Ca HRCF+NPKSB treatment to 98 m3 ha−1 in the control. Differences in response are likely due to soil characteristics, such as organic matter, emphasizing the importance of identifying site-specific nutrient deficiencies.

Financial Returns for Biomass on Short-Rotation Loblolly Pine Plantations in the Southeastern United States - Andrew Trlica; Rachel L Cook; Timothy J Albaugh; Rajan Parajuli; David R Carter; Rafael A Rubilar (Forest Science, 2021)
Rising demand for renewable energy has created a potential market for biomass from short-rotation pine plantations in the southeastern United States. Site preparation, competition control, fertilization, and enhanced seedling genotypes offer the landowner several variables for managing productivity, but their combined effects on financial returns are unclear. This study estimated returns from a hypothetical 10-year biomass harvest in loblolly pine plantation using field studies in the Coastal Plain of North Carolina and the Virginia Piedmont testing combinations of tree genotype, planting density, and silviculture. Although enhanced varietal genotypes could yield more biomass, open-pollinated seedlings at 1,236–1,853 trees ha−1 under operational silviculture had the greatest returns at both sites, with mean whole-tree internal rates of return of 8.3%–9.9% assuming stumpage equal to current pulpwood prices. At a 5% discount rate, break-even whole-tree stumpage at the two sites in the optimal treatments was $8.72–$9.92 Mg−1, and break-even yield was 175–177 Mg ha−1 (roughly 18 Mg ha−1 yr−1 productivity), although stumpage and yield floors were higher if only stem biomass was treated as salable. Dedicated short-rotation loblolly biomass plantations in the region are more likely to be financially attractive when site establishment and maintenance costs are minimized.

A 50-Year Retrospective of the Forest Productivity Cooperative in the Southeastern United States: Regionwide Trials - David R Carter; H Lee Allen; Thomas R Fox; Timothy J Albaugh; Rafael A Rubilar; Otávio C Campoe; Rachel L Cook (Journal of Forestry, 2021)
In 2019, the Forest Productivity Cooperative (FPC) celebrated its 50th anniversary. The mission of the FPC is and has been creating innovative solutions to enhance forest productivity and value through the sustainable management of site resources. This industry-government-university partnership has generated seminal research with sweeping implications for increasing productivity throughout the southeastern United States and Latin America. To commemorate this semicentennial, we highlighted some of the pivotal findings in the southeastern United States from the past 50 years derived from our large, regional experiments: regionwide trials.

Crown architecture, crown leaf area distribution, and individual tree growth efficiency vary across site, genetic entry, and planting density - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marco A. Yáñez; Eric D. Carbaugh; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Trees, 2020)

Forest Fertilizer Applications in the Southeastern United States from 1969 to 2016 - Timothy J Albaugh; Thomas R Fox; Rachel L Cook; Jay E Raymond; Rafael A Rubilar; Otávio C Campoe (Forest Science, 2019)

Advances in Silviculture of Intensively Managed Plantations - Rafael A. Rubilar; H. Lee Allen; Thomas R. Fox; Rachel L. Cook; Timothy J. Albaugh; Otávio C. Campoe (Current Forestry Reports, 2018)

Evaluating changes in switchgrass physiology, biomass, and light-use efficiency under artificial shade to estimate yields if intercropped with Pinus taeda L. - Janine M. Albaugh; Timothy J. Albaugh; Ryan R. Heiderman; Zakiya Leggett; Jose L. Stape; Kyle King; Katherine P. O’Neill; John S. King (Agroforestry Systems, 2014)

Root and stem partitioning of Pinus taeda - Timothy J. Albaugh; H. Lee Allen; Lance W. Kress (Trees, 2006)

Respiratory carbon use and carbon storage in mid‐rotation loblolly pine ( Pinus taeda L.) plantations: the effect of site resources on the stand carbon balance - Chris A. Maier; Timothy J. Albaugh; H. Lee Allen; Phillip M. Dougherty (Global Change Biology, 2004)
We used estimates of autotrophic respiration ( R A ), net primary productivity (NPP) and soil CO 2 evolution ( S ff ), to develop component carbon budgets for 12‐year‐old loblolly pine plantations during the fifth year of a fertilization and irrigation experiment. Annual carbon use in R A was 7.5, 9.0, 15.0, and 15.1 Mg C ha −1 in control (C), irrigated (I), fertilized (F) and irrigated and fertilized (IF) treatments, respectively. Foliage, fine root and perennial woody tissue (stem, branch, coarse and taproot) respiration accounted for, respectively, 37%, 24%, and 39% of R A in C and I treatments and 38%, 12% and 50% of R A in F and IF treatments. Annual gross primary production (GPP=NPP+ R A ) ranged from 13.1 to 26.6 Mg C ha −1 . The I, F, and IF treatments resulted in a 21, 94, and 103% increase in GPP, respectively, compared to the C treatment. Despite large treatment differences in NPP, R A , and carbon allocation, carbon use efficiency (CUE=NPP/GPP) averaged 0.42 and was unaffected by manipulating site resources. Ecosystem respiration ( R E ), the sum of S ff , and above ground R A , ranged from 12.8 to 20.2 Mg C ha −1 yr −1 . S ff contributed the largest proportion of R E , but the relative importance of S ff decreased from 0.63 in C treatments to 0.47 in IF treatments because of increased aboveground R A . Aboveground woody tissue R A was 15% of R E in C and I treatments compared to 25% of R E in F and IF treatments. Net ecosystem productivity (NEP=GPP‐ R E ) was roughly 0 in the C and I treatments and 6.4 Mg C ha −1 yr −1 in F and IF treatments, indicating that non‐fertilized treatments were neither a source nor a sink for atmospheric carbon while fertilized treatments were carbon sinks. In these young stands, NEP is tightly linked to NPP; increased ecosystem carbon storage results mainly from an increase in foliage and perennial woody biomass.

Stand-Scale Correspondence in Empirical and Simulated Labile Carbohydrates in Loblolly Pine - David A. Sampson; Kurt H. Johnsen; Kim H. Ludovici; Timothy J. Albaugh; Chris A. Maier (Forest Science, 2001)
As investment into intensive forestry increases, the potential trade-offs between productivity and sustainability should be scrutinized. Because of their important role in internal carbon (C) budgets, labile C pools may provide a measure of the potential ability of trees and stands to respond to stress. We modified the process model BIOMASS to examine daily C budgets of midrotation nonfertilized and fertilized loblolly pine stands. We tested whether the absolute difference between daily simulated net canopy assimilation (GPP minus maintenance respiration) and our empirical estimates of production, or daily gross carbon balance, mimics the labile carbohydrate C pool. We compared this labile pool surrogate to independent, empirical analyses of total nonstructural (starch and soluble sugars) carbohydrates from an individual whole-tree analysis scaled to the stand level.Of particular interest, the simulated daily gross C balance indicated periods of carbon deficit during the growing season that lasted from 1 to 40 days. Simulated daily net C balance was met from labile C storage during these periods. Fertilized plots had similar time-period trends as the control plots, but exhibited a twofold increase in C assimilation and use. Simulated and empirical estimates of the labile carbohydrate pools displayed similar seasonal trends, although their correspondence depended on the time of year. Simulations indicated a winter/early spring “recharge” period; concentrations peaked at ~50 and ~60 mg C g biomass-1 in control and fertilized plots, respectively, in 1995. The overall correlation between predicted and empirical estimates was low to moderate (r = 0.51). The best agreement was with the empirical data from April through June as concentrations declined; however, predicted minimum concentrations (15 and 5 mg C g biomass-1 in control and fertilized plots, respectively) were lower, and obtained earlier in the year than the empirical data (~20 mg C mg biomass-1). These analyses quantify the strong extent that loblolly pine exhibits a buffered capacity to balance the C budget when current photosynthesis occasionally cannot meet daily C requirements. Further development of our approach may lead to a tool for analyzing potential risks associated with intensive forest management. FOR. Sci. 47(1):60–68.

Applying 3-PG, a Simple Process-Based Model Designed to Produce Practical Results, to Data from Loblolly Pine Experiments - Joe J. Landsberg; Kurt H. Johnsen; Timothy J. Albaugh; H. Lee Allen; Steven E. McKeand (Forest Science, 2001)
3-PG is a simple process-based model that requires few parameter values and only readily available input data. We tested the structure of the model by calibrating it against loblolly pine data from the Control treatment of the SETRES experiment in Scotland County, NC, then altered the Fertility Rating to simulate the effects of fertilization. There was excellent correspondence between simulated values of stem mass and the values obtained from field measurements, and good correspondence between simulated and measured stem diameters and Leaf Area Index values. Growth efficiency values derived from the model were similar to those obtained from field data. We used the model, without further calibration, to predict tree growth in terms of stem diameter at SETRES 2, a genotype × environment interaction trial in the same locality. Simulated mean stem diameters of two provenances did not differ significantly, over 3 yr, from those observed in the Control (unfertilized) treatments, but rates of change were lower than those of fertilized provenances. We then used 3-PG to simulate fertilized stand growth for an entire rotation length, and these results corresponded to those obtained with a traditional growth and yield model. This study showed that the model can simulate accurately the behavior and responses to environmental factors of loblolly pine and that it has considerable potential value as a management tool, for scenario analysis and as a research tool. FOR. Sci. 47(1):43–51.

Leaf Area and Above- and Belowground Growth Responses of Loblolly Pine to Nutrient and Water Additions - Timothy J. Albaugh; H. Lee Allen; Phillip M. Dougherty; Lance W. Kress; John S. King (Forest Science, 1998)
A 2 x 2 nutrient and water factorial experiment with four replications was installed in an 8-yr-old stand of loblolly pine (Pinus taeda L.) growing on an infertile, excessively drained sandy site in Scotland County, North Carolina. After the fourth year of treatment, estimated stem volume increment, total biomass production, and peak leaf area index (LAI) increased 152%, 99%, and 101%, respectively, with fertilization and 25%, 23%, 16%, respectively, with irrigation. Stem volume growth efficiency (growth per unit LAI) increased 21% with fertilization, 9% with irrigation, and 30% with both fertilization and irrigation. Total biomass production efficiency increased 91% with fertilization, 29% with irrigation, and 120% with both fertilization and irrigation. The observed increase in stem volume growth efficiency may have been due, in part, to changes in biomass partitioning. However, altered partitioning patterns alone did not explain the observed increase in total biomass production efficiency. We hypothesized that the change in total biomass production efficiency may have been a result of greater allocation to foliage (photosynthesizing tissue) and less allocation to fine roots (a high maintenance respiration tissue) under fertilization and irrigation treatments. For. Sci. 44(2):317-328.